SINTESIS NANOPARTIKEL PERAK (NPAg) DENGAN BIOREDUKTOR EKSTRAK BIJI JARAK PAGAR DAN KAJIAN AKTIVITAS ANTIBAKTERINYA - Ara Nugrahayu Nalawati; Nugraha Edhi Suyatma; Danu Indra Wardhana (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2021)
The redox analysis as indicated by a change in color from yellow to reddish-brown was measured at the optimum wavelength of 405 nm with the highest redox result of 480 nm obtained in the NPAg-S sample. The optimal absorption wavelength changes according to the characteristics of the NPAg produced, but is generally in the range of 400-500 nm. Analysis of the active groups with the FTIR instrument showed active groups (OH, CH aldehyde, vibrations of CN bonds in the amine group, amide I groups from proteins, and CO double bonds in the 4000-1500 cm-1) zone. Additionally, in the identification zone 1500-600 cm-1 the formation of CN bond vibrations and the presence of an amide I group from the protein was found. Photographs at 10.000 and 15.000x magnification showed that the morphology of the distribution of NPAg in the jatropha seed extract solution was polydisperse and in the form of fibrous balls with non-uniform particles and tended to agglomerate. The distribution and size of the particles measured using the Particle Size Analyzer (PSA) instrument showed that the particle size ranged from 33-116 nm. NPAg-S samples at two concentrations (1 and 2%) showed inhibitory activity for all types of Gram positive and Gram negative bacteria. Analysis of the particle size distribution using PSA showed that the particle size of the NPAg-S sample was 33.8 nm, which was smaller than the NPAg-K sample of 44.8 nm. Antibacterial activity is strongly influenced by the particle size of a sample. Small size silver nanoparticles have a large surface area to interact with bacteria as compared to large silver nanoparticles, thus they can provide a greater antibacterial effect.